Uma abordagem integrada de desenvolvimento e teste de software para equipes distribuídas - Leal, Gislaine Camila Lapasini (2010)
The Distributed Software Development (DSD) is a development strategy that meets the globalizations needs in relation to productivity and cost reduction. However, it added new elements to the development process, such as the temporal distance, geographical dispersion and the socio-cultural differences, which amplified some challenges and, especially, added new requirements in relation to the communication process, coordination and control of projects. Among these new demands there is the necessity of a software process that provides suited support to the distributed software development. This work presents an integrated approach of software development and test that considers the peculiarities of distributed teams. The goal of the approach is to offer support to the strategy of development, providing a better visibility of a project, improving the communication between the development and test teams, minimizing the ambiguity and difficulty in understanding the artifacts and activities. This integrated approach was conceived based on four pillars: (i) to identify the peculiarities of Distributed Software Development related to development and test processes, (ii) to define the necessary elements to compose the integrated approach of development and test to support the distributed teams, (iii) to describe and specify the workflows, artifacts, and roles of the approach, and (iv) to represent appropriately the approach to enable the effective communication and understanding of it. The approach was evaluated, using the Experimental Engineering principles, by conducting a feasibility study.